DEMANDA HÍDRICA E ADUBAÇÃO ORGÂNICA NO CULTIVO PROTEGIDO DE PIMENTÃO NA REGIÃO NORTE DA BAHIA - Souza, Ruanna Matos Almeida; Leitão, Mário de Miranda Vilas Boas Ramos; Oliveira, Gertrudes Macário de; Oliveira, Emerson Damasceno de; Correia, Leonardo Torres (IRRIGA, 2021)
DEMANDA HÍDRICA E ADUBAÇÃO ORGÂNICA NO CULTIVO PROTEGIDO DE PIMENTÃO NA REGIÃO NORTE DA BAHIA RUANNA MATOS ALMEIDA SOUZA¹; MÁRIO DE MIRANDA VILAS BOAS RAMOS LEITÃO²; GERTRUDES MACÁRIO DE OLIVEIRA³; EMERSON DAMASCENO DE OLIVEIRA4 E LEONARDO TORRES CORREIA5 ¹ Colegiado de Engenharia Agrícola e Ambiental, Universidade Federal do Vale do São Francisco, UNIVASF, Av. Antônio C. Magalhães, 510, Country Club, Juazeiro - BA, CEP: 48902-300, ruanna.matos@outlook.com ² Colegiado de Engenharia Agrícola e Ambiental, Universidade Federal do Vale do São Francisco, UNIVASF, Av. Antônio C. Magalhães, 510, Country Club, Juazeiro - BA, CEP: 48902-300, mario.miranda@univasf;edu.br ³ Departamento de Tecnologia e Ciências Sociais, Universidade do Estado da Bahia, UNEB, Av, R. Edgar Chastinet, s/n - São Geraldo, Juazeiro - BA, CEP: 48900-000, gemoliveira@uneb.br 4 Colegiado de Engenharia Agrícola e Ambiental, Universidade Federal do Vale do São Francisco, UNIVASF, Av. Antônio C. Magalhães, 510, Country Club, Juazeiro - BA, CEP: 48902-300, emerson.oliveira@univasf.edu.br 5 Colegiado de Engenharia Agrícola e Ambiental, Universidade Federal do Vale do São Francisco, UNIVASF, Av. Antônio C. Magalhães, 510, Country Club, Juazeiro - BA, CEP: 48902-300, leonardo.torrescorreia@hotmail.com 1 RESUMO Palavras-chave: evapotranspiração, irrigação, coeficiente de cultivo. MATOS, R.M.A; LEITÃO,M.DE M.V.B.R; OLIVEIRA, G.M.DE; OLIVEIRA, E. D. DE;CORREIA, L. T. WATER DEMAND AND ORGANIC FERTILIZATION IN PROTECTED PIMENTÃO CULTIVATION IN THE NORTH REGION OF BAHIA 2 ABSTRACT The objective was to determine crop evapotranspiration (ETc), crop coefficient and water use efficiency for the production of sweet pepper (Capsicum annuum L.) cultivated under two soil compounds in a protected environment. The experiment was conducted in Juazeiro-BA, from June to October 2019. The pepper was grown in pots, the design was randomized blocks, split plots, four irrigation depths were used (95, 100, 105 and 110% of ETc) and two levels of soil fertilization: A1 (25% manure and 75% soil) and A2 (40% manure and 60% soil), which were based on studies developed by Santana (2019). ETc was determined using two sets of constant water table lysimeters and the crop coefficient was determined from ETc and reference evapotranspiration. The total water demand of the crop for the A1 fertilization level was 527.3 mm and for that A2 was 395.7 mm. The maximum and minimum crop coefficients were respectively 0.78 and 0.23 for A2; 1.02 and 0.34 for A1. The A1 level of fertilization showed higher productivity and satisfactory conversion of water into fresh fruit mass. Keywords: evapotranspiration, irrigation, crop coefficient.